TRANSFORMASI BUJANG GADIH AT RANDAI’S SHOW TELUK KUANTAN, PROVINSI RIAU - MISRAWATI MISRAWATI; SULAIMAN SULAIMAN (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
Bujang Gadih is the main character in the Teluk Kuantan Randai show. Bujang Gadih is a man who plays like a woman with the Bertold Brecht hich is entertaining and educational. The role of Bujang Gadih in the show Randai Teluk Kuantan become Randai identity in the Teluk Kuantan even all regions of Riau Province. This shows that the social transformation that occurred in the Teluk Kuantan community has constructed a Randai in accordance with the culture that is formed. This article aims to discuss the social transformation that forms Bujang Gadih as the main character in the Teluk Kuantan Randai show, so Bujang Gadih becomes its own identity in Randai in Teluk Kuantan. This study uses a qualitative method that is passed through observation, interviews, data analysis and documentation on the object of research and those related to the object. Research result Bujang Gadih in Randai Teluk Kuantan is a representation of social transformation that makes the identity of one of the arts of the Teluk Kuantan namely, Randai Teluk Kuantan.